Lightning Interaction with Power Systems. Volume 2, - Piantini, Alexandre (IET energy engineering series, 2020)
This book assesses how global lightning may respond to global climate change, provides thorough coverage of the lightning phenomenon and its interaction with various objects, and covers methods for the effective protection of structures and systems.